2003
DOI: 10.1093/pcp/pcg172
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis-accelerated cell death Gene ACD1 is Involved in Oxygenation of Pheophorbide a: Inhibition of the Pheophorbide a Oxygenase Activity does not Lead to the “Stay-Green” Phenotype in Arabidopsis

Abstract: Oxygenation of pheophorbide a is a key step in chlorophyll breakdown. Several biochemical studies have implicated that this step was catalyzed by an iron-containing and ferredoxin-dependent monooxygenase, pheophorbide a oxygenase (PaO). It has been proposed that inhibition of its activity arrests the chlorophyll breakdown and leads to the "stay-green" phenotype. We searched the Arabidopsis genome for a possible PaO-encoding gene and hypothesized that it has homology to known iron-containing Rieske-type monooxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 49 publications
4
141
0
1
Order By: Relevance
“…It is interesting to notice that spc1-1 has a lower level of chlorophylls a and b, which appears to be correlated to the reduced expression of PORB and CAO. The impaired chlorophyll metabolism and abnormal chloroplast development have been attributed as an important mechanism to trigger spontaneous cell death in a number of mutants, including Arabidopsis-accelerated cell death2 (acd2) [63,64], acd1 [65][66][67] and maize lethal leaf spot-1 (lls1) [68,69]. ACD1 and LLS1 are believed to be ortholog genes in Arabidopsis and maize [65,66,69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to notice that spc1-1 has a lower level of chlorophylls a and b, which appears to be correlated to the reduced expression of PORB and CAO. The impaired chlorophyll metabolism and abnormal chloroplast development have been attributed as an important mechanism to trigger spontaneous cell death in a number of mutants, including Arabidopsis-accelerated cell death2 (acd2) [63,64], acd1 [65][66][67] and maize lethal leaf spot-1 (lls1) [68,69]. ACD1 and LLS1 are believed to be ortholog genes in Arabidopsis and maize [65,66,69].…”
Section: Discussionmentioning
confidence: 99%
“…The impaired chlorophyll metabolism and abnormal chloroplast development have been attributed as an important mechanism to trigger spontaneous cell death in a number of mutants, including Arabidopsis-accelerated cell death2 (acd2) [63,64], acd1 [65][66][67] and maize lethal leaf spot-1 (lls1) [68,69]. ACD1 and LLS1 are believed to be ortholog genes in Arabidopsis and maize [65,66,69]. These three genes, all encoding key enzymes for chlorophyll degradation, presumably function to prevent the formation of ROS or free radicals generated from photooxidation, thereby negatively regulating cell death [63,64,69].…”
Section: Discussionmentioning
confidence: 99%
“…This is explained, at least in part, by the substrate specificity of PAO for pheophorbide (Pheide) a (Hörtensteiner et al 1995) and suggests that conversion of Chl b to Chl a is a prerequisite for further degradation via PAO. However, mutants that are devoid of PAO specifically accumulate Pheide a (Tanaka et al 2003;Pružinská et al 2003), indicating that conversion of Chl b to Chl a occurs upstream of Pheide formation.…”
Section: Chlorophyll Catabolic Enzymesmentioning
confidence: 99%
“…As mentioned above, PAO exhibits an intriguing specificity for Pheide a, with Pheide b being a competitive inhibitor. In 2003, two groups succeeded in identifying Arabidopsis PAO at the molecular level (Pružinská et al 2003;Tanaka et al 2003). PAO is identical to ACCELERATED CELL DEATH (ACD) 1 (Greenberg and Ausubel 1993) and the ortholog of LETHAL LEAF SPOT 1 in maize (Gray et al 1997).…”
Section: Mg-dechelation and Dephytylationmentioning
confidence: 99%
“…Mur et al (2010) showed that reactive oxygen species caused chlorophyll degradation in the course of Pseudomonas syringae infection and that light-excited products of chlorophyll degradation, e.g., pheophorbide a (Pheide) may be an additional source of ROS. It was suggested in several other studies that pheophorbide a can act as a photosensitizer that generates ROS in response to light (Tanaka et al 2003;Hörtensteiner 2004;Pruzinska et al 2005;Tanaka and Tanaka 2006). Pheophorbide a content was not analyzed in this study.…”
Section: Discussionmentioning
confidence: 93%